Measurement of the production cross sections for a Z boson and one or more b jets in pp collisions at sqrt(s) = 7 TeV - CMS collaboration (2221 authors); Hollar, Jonathan; Nayak, Aruna; Calpas, Betty; Almeida, Nuno; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Nguyen, Federico; Rodrigues Antunes, Joao; et al. (My University, 2014)
The production of a Z boson, decaying into two leptons and produced in association with one or more b jets, is studied using proton-proton collisions delivered by the LHC at a centre-of-mass energy of 7 TeV. The data were recorded in 2011 with the CMS detector and correspond to an integrated luminosity of 5 fb(−1). The Z(ℓℓ) + b-jets cross sections (where ℓℓ = μμ or ee) are measured separately for a Z boson produced with exactly one b jet and with at least two b jets. In addition, a cross section ratio is extracted for a Z boson produced with at least one b jet, relative to a Z boson produced with at least one jet. The measured cross sections are compared to various theoretical predictions, and the data favour the predictions in the five-flavour scheme, where b quarks are assumed massless. The kinematic properties of the reconstructed particles are compared with the predictions from the MadGraph event generator using the pythia parton shower simulation.